Influence of work systems and lost time in the calculation of equipment for open pit mining of the Antilla deposit, Apurímac - Ortiz Sánchez, Oswaldo (2011)
The Antilla ore body open pit mining equipment is estimated for a total movement of 544 million metric tons of ore and waste in 20 years of active operation. Mining equipment is evaluated from the point of view of 3 working systems and time savings on the performance system. Three working alternatives are analyzed: Alternative 1 consists of three-8 hour shifts per day, six day per week operation. Alternative 2 includes three-8 hour shifts per day, 7 day per week and alternative 3 consists of four-six hour shifts per day 7 day per week work. Equipment size is chosen as a function of daily production, pit geometry, bench height, working angle and space requirements for safe operation of each equipment. Performance parameters used in equipment estimation were taken from 3 similar mining operations. Lost time analysis on the equipment performance were also considered in order to improve utilization of the 4 types of equipment required in the open pit operation.